Assessment of environmental and surgical mask contamination at a student health center — 2012–2013 influenza season. Issue 9 (2nd September 2018) - Ahrenholz, Steven H.; Brueck, Scott E.; Rule, Ana M.; Noti, John D.; Noorbakhsh, Bahar; Blachere, Francoise M.; de Perio, Marie A.; Lindsley, William G.; Shaffer, Ronald E.; Fisher, Edward M.
Abstract: Increased understanding of influenza transmission is critical for pandemic planning and selecting appropriate controls for healthcare personnel safety and health. The goals of this pilot study were to assess environmental contamination in different areas and at two time periods in the influenza season and to determine the feasibility of using surgical mask contamination to evaluate potential exposure to influenza virus. Bioaerosol samples were collected over 12 days (two 6-day sessions) at 12 locations within a student health center using portable two-stage bioaerosol samplers operating 8 hr each day. Surface samples were collected each morning and afternoon from common high-contact non-porous hard surfaces from rooms and locations where bioaerosol samplers were located. Surgical masks worn by participants while in contact with patients with influenza-like illness were collected. A questionnaire administered to each of the 12 participants at the end of each workday and another at the end of each workweek assessed influenza-like illness symptoms, estimated the number of influenza-like illness patient contacts, hand hygiene, and surgical mask usage. All samples were analyzed using qPCR. Over the 12 days of the study, three of the 127 (2.4%) bioaerosol samples, 2 of 483 (0.41%) surface samples, and 0 of 54 surgical masks were positive for influenza virus. For the duration of contact that occurred with an influenza patient on any of the 12 days, nurse practitioners and physicians reported contacts with influenza-like illness patients >60 min, medical assistants reported 15–44 min, and administrative staff reported <30 min. Given the limited number of bioaerosol and surface samples positive for influenza virus in the bioaerosol and surface samples, the absence of influenza virus on the surgical masks provides inconclusive evidence for the potential to use surgical masks to assess exposure to influenza viruses. Further studies are needed to determine feasibility of this approach in assessing healthcare personnel exposures. Information learned in this study can inform future field studies on influenza transmission.